NILAI-NILAI SHOLAWAT WAHIDIYAH DALAM MENUMBUHKAN KECERDASAN SPIRITUAL DAN AKHLAKUL KARIMAH - Fajri, Barlian; Biantoro, Oktio Frenki (Jurnal Pendidikan Islam, 2023)
Islamic education, especially in today's modern era, seems more inclined to develop knowledge (religious science and general science) only limited to "knowledge for knowledge", so that what happens is the accumulation of knowledge that measures success in the cognitive aspect. The method used in this research is a qualitative research method. The data collection techniques used were observation, in-depth interviews, and documentation of research data starting from photos of activities and also data obtained from students and teachers of tasawuf wahidiyah education. Data analysis techniques used by researchers are data reduction, data presentation, and inference. The results of this study are the Wahidiyah Sufism education model in cultivating spiritual intelligence and Akhlakul Karimah done through two approaches. First, through the practice of mujahadah, namely reading the Wahidiyah sholawat with deep appreciation, causing students to feel the presence of Allah and the Messenger of Allah and presenting the heart and through learning in the classroom, Seminars, Teaching and Guidance of Da'i Wahidiyah. The implications of Wahidiyah tasawuf education for the development of spiritual intelligence are an attitude of feeling a need for Allah SWT, strengthening social intelligence, developing strong beliefs, and applying a sincere attitude. The educational implications of Wahidiyah Tasawuf in fostering akhlakul karimah is the growth of high moral and ethical values ​​such as decency, honesty, justice, hard work, kindness, tolerance, and mutual respect.